3dways internationalization project - in-depth analysis of the Netherlands 2019/2020 - Sousa, Jessica Elizabeth (2020)
3DWays is a 3Dprinting service-providing company. Currently ,the company wantsto internation alizeits remotely managed network of 3Dprinting factories ,specifically targeting at the health care sector. The refore, this project analyses the current and future state of the 3DPrinting industry, before assessing potential target markets. Subsequently, five countries, hea dlinedby the United Kingdom, were determined to be the most suitable for the company’s internationalization that will relyon direct exporting as an entry strategy because of the unique nature of the network. Complementary, a marketing plan and a financial evaluation were developed for 3DWays in the UK. 3DWays ,Internationalization ,3DPrinting, Competitiveness